A Disposable Electrochemical Sensing Platform for Acetaminophen Based on Graphene/ZrO2 Nanocomposite Produced via a Facile, Green Synthesis Method - Lin, Lih Poh; Khiew, Poi Sim; Chiu, Wee Siong; Tan, Michelle T.T. (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In this paper, a disposable electrochemical sensor was fabricated using graphene/zirconium dioxide (ZrO2)-modified screen printed carbon electrode (SPCE). The implemented synthesis route is simple, cost feasible, and abolish the usage of harsh chemical. A green approach using single step exfoliation of graphite in mild sonochemical ethanol-water treatment and hydrothermal synthesis method were employed to prepare the graphene/ZrO2 nanocomposites. Characterization methods, such as X-ray diffraction, scanning electron microscope (SEM), transmission electron microscopy (TEM), high resolution TEM (HRTEM) and energy dispersive x-ray spectroscopy (EDX), were used to study the crystallinity, surface characteristics, morphology and elemental composition of the synthesized nanocomposites. All the results evidently suggested that pristine graphene was successfully produced without attachment of any undesirable functional groups and ZrO2 nanoparticles of approximately 10.4 nm were homogeneously distributed on the graphene sheet. The electrochemical performance of the graphene/ZrO2/SPCE was assessed with cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Both tests suggested improved electron transfer kinetic of graphene/ZrO2/SPCE as compared with bare SPCE. Effect of ZrO2 precursor loading was investigated, in which nanocomposites containing different ratios of graphene and ZrO2 precursors were prepared. CV and EIS results indicated that ratio 1:8 (graphene: ZrO2 precursor) was the optimum composition, exhibiting the highest current response and lowest charge transfer resistance. The potential application of graphene/ZrO2/SPCE for electroanalytical purposes was demonstrated with acetaminophen detection. The graphene/ZrO2/SPCE sensor was calibrated with differential pulse voltammetry and demonstrated better electrocatalytic activity toward acetaminophen with lower oxidation potential and higher peak current than the unmodified SPCE. The sensor exhibited a linear range of 10-100~μ \text{M} , detection limit of 75.5 nM, reproducibility of <5 % relative standard deviation (RSD), repeatability of < 3% RSD, and good selectivity to acetaminophen in the presence of dopamine and ascorbid acid. The graphene/ZrO2/SPCE sensor was applied to determine acetaminophen in pharmaceutical tablets and yielded satisfactory results. The simple, low cost, and green method reported here can be further exploited to provide a biocompatible platform for electrochemical sensing application.